Pollinator cultivar choice: An assessment of season-long pollinator visitation among coreopsis, aster, and salvia cultivars - Braman, S. K.; Pennisi, S. V.; Fair, C. G.; Quick, J. C. (Frontiers in Sustainable Cities, 2022)
Documented pollinator declines have encouraged the installation of pollinator plantings in residential, commercial and agricultural settings. Pollinator visitation among cultivars of coreopsis, salvia and asters was compared on 40 dates in a 2-year study resulting in 6,911 pollinator observations across all plant taxa with bees, butterflies and syrphids well-represented. Diversity of insect visitors was represented differently within the broad plant taxa salvia, coreopsis and asters. The most frequent visitors to coreopsis were the small bees with over 77% of visitors falling into this category. Salvia was most frequently visited by honey bees (36.4%) and carpenter bees (24%), although all the groups were represented. Syrphids were the group most commonly observed on asters (58.5%) with nearly 40% of the visitors being bee species. Nectar analysis was performed on salvia cultivars. However, differential attraction of pollinators to salvia cultivars could not be explained by volume of nectar produced per plant. Results from our cultivar comparisons provide data-based information to assist consumers in plant choice and present opportunities for future plant-specific pollinator census initiatives across a broader geographic range.